TEXTBOOK SELECTION EXPERIENCES AMONG SECONDARY SCHOOL TEACHERS OF ENGLISH IN KENYA - KIAI, ALICE W.; MAROKO, GEOFFERY M. (International Journal of Education and Research, 2013)
Textbook development and selection in Kenya has undergone significant change in the last decade. The aim of this paper is to highlight the textbook selection guidelines laid down by the Ministry of Education, and to explore the actual textbook selection experiences among secondary school teachers of English following curriculum review in 2002 and introduction of subsidized secondary education in 2008. Data from interviews in 2010 showed that teachers were not involved in as rigorous a textbook selection procedure as advocated by the Ministry of Education. Textbooks were selected based on factors such as brand recognition, marketing by publishers, teacher-to-teacher influence, and learner level. While teachers generally appreciated increased textbook choices, they suggested various ways in which the textbook selection process can be improved. It is important to highlight teachers’ textbook selection experiences, raise their concerns and explore their insights in a liberalising textbook market where choice has exponentially increased.
Keywords: Textbook development; Textbook selection; Circuit of Culture